Morphometric analysis of posterior fossa in Indian CP angle acoustic schwannoma patients - Patibandla, Mohana; Panigrahi, Manas; Gurram, Paniraj; Thotakura, Amit; Kulkarni, Dilip (Asian Journal of Neurosurgery, 2016)
Aim: To study the morphometry of posterior fossa in Indian CP angle schwannoma patients in order to know its influence on the extent of excision of the CP angle acoustic schwannomas. Materials and Methods: One hundred cases of cerebellopontine angle schwannomas treated surgically by the senior author and 20 controls between January 2006 and June 2011 were consecutively investigated with computed tomography (CT) using the high-resolution CT bone windows before surgery. Evaluation of anatomic parameters of the petrous bone and posterior fossa cavity were done in all patients and controls. Data were entered in Excel software and were analyzed using NCSS software. All possible regression analysis was done to select the important variables to be included in the model to predict the excision of tumor with these variables. A prediction model was developed defining the binary outcome as total excision or subtotal excision as dependent variable and the morphometric data and grading of tumor as independent variables. Results: Interpetrous distance (IP) is the distance between the two petrous apices. Sigmoid distance (IS) distance is the distance between the two sigmoid points. Sigmoid point is the point at which the scalloped impression of the sigmoid sinus straightens to join the occipital bone posteriorly. SAG is the distance between the mid IP point and the mid-point on the inner wall of the occipital bone. The PM angle was 47.8±4.14 degrees (38-58), the PA angle was 42.68±4.47 degrees (34-53), the IP distance was 2.07±0.13 cm (1.5-2.8), the sagittal diameter of posterior fossa was 6.22±0.73 cm (5.1-9.8) and the intersigmoid distance was 9.45±0.73 cm (7.4-11). There was no significant gender difference in the posterior fossa morphometry between patients and controls. Inter-sigmoid distance and the petrous-apex angle were more in the Indians when compared to the European population mentioned in the Mathies and Samii study. Conclusions: The posterior fossa morphological parameters of the Indian and European population differ significantly. Inter-sigmoid distance and the petrous-apex angle were more in the Indians when compared to the Europeans. There is no significant gender difference in the morphometry of the Indians. There is no significant difference between the patients and the control groups. In our study the adhesions with surrounding structures along with the posterior fossa morphometry significantly affect the extent of excision.
Keywords: Angles; cerebellopontine angle angle tumors; morphometry; posterior fossa; schwannoma